A biaxial stretched β‐isotactic polypropylene microporous membrane for lithium‐ion batteries. Issue 6 (5th October 2017) - Yang, Shuting; Gu, Jifeng; Yin, Yanhong
ABSTRACT: In this article, microporous polypropylene (PP) membranes were produced with TMB‐5 as β‐crystal nucleating agent by biaxial stretching. Influences of different concentration of TMB‐5 were studied using differential scanning calorimetry and X‐ray diffraction. It was found that the highest crystallinity was reached when the nucleating agent content was 0.5 wt %. The effect of stretching temperature and stretching ratio on pore size distribution and porosity of the membranes were investigated by scanning electron microscopy and mercury porosimeter, respectively. And physical properties, such as tensile strength, permeability, and puncture resistance of the microporous membrane prepared at the optimized conditions, were evaluated. Compared with commercial PP separator membrane, the as‐prepared microporous membrane shows similar uniform pore size distribution and exhibits slightly higher porosity and ionic conductivities. When used as lithium‐ion separator, the experimental film shows more stable cycling performance than the commercial one. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45825. Abstract :